The Overlapping Consensus in the Indonesian Constitution and Its Challenges: Konsensus Berkeadilan dalam Konstitusi Indonesia dan Tantangan-tantangannya - Sunaryo, Sunaryo (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
Pancasila and UUD 1945 form the foundation of Indonesia's social unity. This article analyzes whether Pancasila and UUD 1945 align with John Rawls' criteria of overlapping consensus. The article concludes that the agreement among Indonesia's founding fathers fulfills the requirements of an